Kualitas Kebersihan Drainase di Kecamatan Panakkukang, Kota Makassar - Jihan Safitri Indriyani; Sandra Sarika; Wanda Kurnia Inri; Jaynart Hizkia; Andreadmaja Andreadmaja (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2020)
Panakkukang Subdistrict is one of the districts that has experienced rapid development in Makassar City, causing various urban problems, one of which is inundation and flooding due to a drainage system that is not functioning optimally. The aim of this research is to determine the problems of drainage infrastructure in Panakkukang District. The time and location of the research were started on October 2019 to July 2020 in Panakkukang District. The data used in this study are secondary data (population, type of building function, standard gross water discharge volume) and primary data (existing conditions of drainage networks and road networks). Secondary data collection is done through literature studies (theory and NSPK) and primary data through observation and documentation. The research method used is descriptive analysis method with qualitative and quantitative approaches. The results showed that problems with drainage infrastructure were found, mostly due to the lack of public awareness about environmental hygiene and the lack of discipline to dispose of garbage in its place. This can be seen from the large amount of garbage that has inundated several drainage points in the Panakkukang District, causing inundation and even flooding.